2014
DOI: 10.1371/journal.pone.0102596
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Second Malignancies for Prostate Cancer

Abstract: IntroductionThere is a need to assess risk of second primary cancers in prostate cancer (PCa) patients, especially since PCa treatment may be associated with increased risk of second primary tumours.MethodsWe calculated standardized incidence ratios (SIRs) for second primary tumours comparing men diagnosed with PCa between 1980 and 2010 in the Canton of Zurich, Switzerland (n = 20,559), and the general male population in the Canton.ResultsA total of 1,718 men developed a second primary tumour after PCa diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 18 publications
3
33
0
Order By: Relevance
“…They found an increased risk of SPCs among men with prostate cancer, compared to the general population (SIR: 1.11, 95% CI: 1.06–1.17). The inconsistency between these two studies may be due to the diagnosis of prostate cancer at an advanced stage with shorter survival in the earlier years of study . Therefore, the chance of developing a SPC was lower than what it is currently, when prostate cancer is generally diagnosed at a less advanced stage.…”
Section: Igf‐1 In Second Primary Cancersmentioning
confidence: 96%
“…They found an increased risk of SPCs among men with prostate cancer, compared to the general population (SIR: 1.11, 95% CI: 1.06–1.17). The inconsistency between these two studies may be due to the diagnosis of prostate cancer at an advanced stage with shorter survival in the earlier years of study . Therefore, the chance of developing a SPC was lower than what it is currently, when prostate cancer is generally diagnosed at a less advanced stage.…”
Section: Igf‐1 In Second Primary Cancersmentioning
confidence: 96%
“…This precluded us from performing any analysis involving these variables. Third, the overall duration of the present study was 11 years, shorter than those of previous studies [8, 11]. Longer follow-up periods are necessary to examine the real effect of RT-induced malignancies.…”
Section: Discussionmentioning
confidence: 89%
“…There is a trend for a higher risk of developing SPMs in the urinary bladder (adjusted SHR = 1.34, 99.72% CI = 1.07–1.69, p = 0.015) and rectum/anus (adjusted SHR = 1.16, 99.72% CI = 0.99–1.37, p = 0.114). The SEER Program [8] and other large population-based studies [10, 11, 12, 14] reported that men with PCa had a 5%–109% increase in the relative risk of urinary bladder cancer compared to the general population. Elevated risk of SPMs in the kidney was also noted by some authors [8, 9, 11, 12]; in contrast, this finding was absent in this study and some other studies as well [10, 14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations